2014
DOI: 10.3389/fneur.2014.00051
|View full text |Cite
|
Sign up to set email alerts
|

β1-Blockers Lower Norepinephrine Release by Inhibiting Presynaptic, Facilitating β1-Adrenoceptors in Normotensive and Hypertensive Rats

Abstract: Peripheral norepinephrine release is facilitated by presynaptic β-adrenoceptors, believed to involve the β2-subtype exclusively. However, β1-selective blockers are the most commonly used β-blockers in hypertension. Here the author tested the hypothesis that β1AR may function as presynaptic, release-facilitating auto-receptors. Since β1AR-blockers are injected during myocardial infarction, their influence on the cardiovascular response to acute norepinephrine release was also studied. By a newly established met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 33 publications
15
27
0
Order By: Relevance
“…Despite metoprolol being a selective postsynaptic β 1 ‐adrenoceptor inhibitor acting mainly on cardiac receptors, it has been shown that it also lowers plasma norepinephrine levels and release, by inhibiting presynaptic facilitating adrenoceptors in rats 50. This fits very well with our observation of reduced catecholamine levels after chronic metoprolol treatment in stroke animals.…”
Section: Discussionsupporting
confidence: 88%
“…Despite metoprolol being a selective postsynaptic β 1 ‐adrenoceptor inhibitor acting mainly on cardiac receptors, it has been shown that it also lowers plasma norepinephrine levels and release, by inhibiting presynaptic facilitating adrenoceptors in rats 50. This fits very well with our observation of reduced catecholamine levels after chronic metoprolol treatment in stroke animals.…”
Section: Discussionsupporting
confidence: 88%
“…The α 2 AR-mediated auto-inhibition of release of NE and also epinephrine was functional in male WKY but not in the male SHR (4, 5). However, α 2 AR clearly inhibited release of both catecholamines in the female SHR (3).…”
Section: Introductionmentioning
confidence: 84%
“…However, the trauma induced by the surgical procedure activated some secretion of epinephrine, also subjected to receptor-mediated release control (3, 4, 13). Removal of the adrenal glands did not alter the plasma NE concentration, indicating that tyramine stimulated the release of NE from sympathetic nerves rather than from NE-producing cells in the adrenal medulla (5). The tyramine-induced NE release activated a cardiovascular response.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations